PERSEPSI PENGURUS MASJID TENTANG PRODUK TABUNGAN BANK SYARIAH DAN MINAT MENABUNG DI BANK SYARIAH (Studi di Kelurahan Simpang IV Sipin Kecamatan Telanaipura Jambi) - Eni Yuspika (Pt. Anagata Sembagi Education, 2024)
This study aims to: (1) to find out how the perception of mosque administrators towards Islamic bank savings products (2) to find out how mosque administrators are interested in saving their mosque funds to Islamic banks. The method used to collect data in this study is through interviews, observation and documentation. In this study, the research objects used were 9 mosques in the Simpang IV Sipin Telanaipura area. The results of this study are that the mosque administrators in the Simpang IV Sipin Telanaipura area there are still some mosque administrators who do not really understand the products issued by Islamic banks, 6 out of 9 mosques studied that the administrators have the perception that Islamic bank products are good, guaranteed by the sharia which is free from usury elements. While the other 3 mosques mosque administrators perceive that Islamic bank products are not much different from conventional banks, they assume that as long as conventional banks do not take excessive profits from customer savings, it is still different if they take profits beyond the limit. Furthermore, as many as 6 mosques, the administrators are interested in saving the mosque funds that they manage in Islamic banks. Meanwhile, as many as 2 mosques, the administrators are not interested in saving the mosque funds that they manage in Islamic banks, they prefer conventional banks. If it is percented, 67% of mosque administrators are interested and 22% of mosque administrators are not interested. Mosque administrators who do not save in Islamic banks because they save in conventional banks, they have the perception that Islamic banks have complicated requirements, difficult and long arrangements, which is why they prefer conventional banks. And 1 mosque administrator is not interested in either Islamic banks or conventional banks, if percented by 11%. The implication of the findings of this study is that it is necessary to follow up on efforts related to increasing public knowledge of Islamic financial products for the better development of Islamic banking, mosques and society.